Industrial canvas and its manufacturing method

A canvas with twisted yarns and a vinyl chloride resin coating layer, incorporating reactive liquid rubbers and silica particles, addresses the issues of tear strength and durability in industrial materials, providing improved handling and longevity.

JP7616707B1Active Publication Date: 2025-01-17HIRAOKA & CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023150634
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-01-17
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

Existing canvases for industrial materials, such as tent warehouses, house tents, and truck bed covers, lack sufficient tear strength, bending durability, and abrasion resistance, especially in extreme temperatures, making them heavy and difficult to handle and store.

Method used

A canvas composed of twisted yarns made of multifilament yarn and short fiber spun yarn, with a soft vinyl chloride resin impregnated coating layer containing a liquid rubber cured product, which includes reactive liquid rubbers and silica particles, enhancing adhesion and durability.

Benefits of technology

The canvas achieves excellent tear strength, bending durability, and abrasion resistance, even when made lighter, allowing for easier handling and longer service life without compromising performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616707000001
    Figure 0007616707000001
  • Figure 0007616707000002
    Figure 0007616707000002
  • Figure 0007616707000003
    Figure 0007616707000003
Patent Text Reader

Abstract

To provide a canvas for industrial materials having excellent tear strength, bending durability (flutter resistance) and abrasion resistance, and a manufacturing method thereof. [Solution] A canvas having a soft polyvinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric, the fabric being woven from a warp yarn group and a weft yarn group, with both the warp and weft yarn groups being composed of twisted yarns made of multifilament yarns / staple fiber spun yarns, the multifilament yarns being bulky yarns or twisted yarns having bulky portions on the outer periphery, the canvas having a soft polyvinyl chloride resin-impregnated coating layer containing a cured liquid rubber, in particular the cured liquid rubber being a polymer of reactive liquid rubber, and if necessary the cured liquid rubber being a complex with silica particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a canvas for industrial materials that has excellent tear strength, flexural durability (flutter resistance) and abrasion resistance and is used as the main material for tent warehouses (simple houses), house tents (assembly tents with awnings that are used for athletic meets, outdoor events, management headquarters, assemblies, reception desks, etc.), truck canopies, truck loading bed covers, open-air storage sheets, etc., and is related to a method for manufacturing the same. [Background technology]

[0002] For the main body material of tent warehouses, roofed tents, truck hoods, truck bed covers, open-air storage sheets, etc., No. 4 to No. 6 canvas, which is made by impregnating and coating No. 4 to No. 6 spun cloth with a soft polyvinyl chloride resin composition, is used. These have a thickness of 0.38 to 0.55 mm and a mass of 420 to 560 g / m 2 The standard is mainstream, and the smaller the number, such as No. 6, No. 5, and No. 4, the heavier and more durable the canvas. The fabric used for these canvases is woven from short fiber spun yarns with a lot of fluff, and the soft polyvinyl chloride resin composition has a high impregnation and coating effect, which gives the canvas its bending strength and bending durability. This bending strength and bending durability exceed those of tarpaulin, but the tear resistance (tear strength) of canvas is inferior to that of tarpaulin, which is based on a fabric woven with multifilament yarn. Therefore, in the above-mentioned applications, the larger the application scale (size), the more emphasis is placed on toughness and tear resistance, and a rank up from No. 6 to No. 5, and from No. 5 to No. 4 canvas is sometimes used. This means an increase in mass for large-scale applications, and especially for applications such as house tents, truck bed covers, and open-air storage sheets, which are folded and stored when stored, the manual transportation, spreading, and installation of the sheets, as well as their removal, are a huge burden. Therefore, for these applications, there is a strong demand for lighter, more durable canvas, for example, a canvas with the weight of No. 6 but the toughness and durability of No. 5, or similarly, a canvas with the weight of No. 5 but the toughness and durability of No. 4.

[0003] In response to such needs, the applicant proposed an invention (Patent Document 1) for a canvas with excellent tear strength due to soft polyvinyl chloride resin processing, in which the weave structure contains parallel yarns consisting of two staple spun yarns, the warp and weft contain parallel yarns, and at least the intersection point of the warp and weft contains a portion composed of four staple spun yarns. In this invention, when comparing canvases using the same fabric size (mass) (Example 1 / Comparative Example 1, Example 2 / Comparative Example 2), a canvas with superior tear strength was obtained, and the effects of the invention were described as being that a canvas was obtained that could exhibit the same tear strength as conventional products while using a lighter fabric than conventional products. The sheet can be used for industrial materials such as waterproof cloth, tarpaulin, tents, truck hoods, etc., and for clothing such as cold weather clothing, and has excellent adhesion to resins and tensile strength, tear strength, etc. The sheet is made of a base fabric (Example 1) knitted or woven with twisted yarns consisting of long fiber yarns and short fiber yarns, or a base fabric (Example 2) knitted or woven with long and short composite twisted yarns, and processed with soft polyvinyl chloride resin to have a basis weight of 450 g / m. 2 The invention of a waterproof fabric (Patent Document 2) has been disclosed. Recently, a flexible laminate that is excellent in strength, water resistance, flexibility, and durability, and has improved lightness due to soft polyvinyl chloride resin processing has been developed, in which the warp and weft yarns constituting the fiber fabric contain one or more selected from spun yarns and multifilament yarns, the content ranges of the spun yarns and multifilament yarns relative to the mass of the fiber fabric are individually specified, and the basis weight of the flexible laminate is set to 300 g / m 2 More than 450g / m 2 In this invention, the flexible laminate in the embodiment has a basis weight of 450 g / m 2It is described that the weight is less than 10% to 25% lighter than the conventional flexible laminate of the comparative example, and the tensile strength, tear strength, and elongation are all equivalent to those of the conventional flexible laminate. However, the invention of Patent Document 3 mainly uses a plain weave base fabric with spun yarn for the warp and multifilament yarn for the weft as Examples 1 to 4, so that in order to achieve a balance in tear strength in the warp and weft directions, it is time-consuming to adjust the yarn strength (fineness) and thread count (yarn arrangement density) in the warp and weft directions, and the appearance has directionality, with streaks in the glossy and diffuse reflection areas being emphasized depending on the angle.

[0004] The canvases of Patent Documents 1 to 3 can improve physical properties such as tear strength and reduce weight by improving the weave of the fabric, using different types of yarns in combination, etc. However, to further reduce weight, it is directly effective to reduce the thickness of the resin coating layer made of soft polyvinyl chloride resin with a high specific gravity, but naturally, making the resin coating layer thinner has a negative effect on bending resistance, abrasion resistance, and joint durability (safety in which the stitching is less likely to peel off and break), and is prone to problems such as water leakage (rain leakage) from cracks and abrasion scratches, and stitching breakage. To avoid these problems, it is essential to reduce the weight (thinning) of the resin coating layer while improving its bending resistance, abrasion resistance, etc.; if the soft polyvinyl chloride resin coating layer can be strengthened, it will be possible to reduce the weight (thinning) to a certain extent without compromising durability, which will reduce the difficulty of fitting and removing the truck bed covers and, further, improving their service life will contribute to an environmentally conscious society that reduces carbon dioxide emissions. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2021-017668 [Patent Document 2] Japanese Patent Application Publication No. 10-96168 [Patent Document 3] Patent Publication No. 2022-057803 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a canvas for industrial materials that has excellent tear strength, flexural durability (resistance to flapping) and abrasion resistance and can be used as the main material for tent warehouses (simple houses), rooftop tents (assembly tents with awnings that can be used for athletic meets, outdoor events, management headquarters, assemblies, reception desks, etc.), truck canopies, truck loading bed covers, open-air storage sheets, etc., and a manufacturing method for the same. [Means for solving the problem]

[0007] As a result of careful research taking into consideration these points, the inventors discovered that a canvas composed of a fabric made of twisted yarns of multifilament yarn / staple fiber spun yarn, and a soft polyvinyl chloride resin-impregnated coating layer containing a liquid rubber cured product, can have excellent tear strength, bending durability (flutter resistance), and abrasion resistance even when the soft polyvinyl chloride resin-impregnated coating layer is made lighter, which led to the completion of the present invention.

[0008] The canvas for industrial materials of the present invention is a canvas having a soft polyvinyl chloride resin-impregnated coating layer on the entire surface of the fabric, the fabric being woven from a warp yarn group and a weft yarn group, the warp and weft yarn groups being composed of a multifilament yarn / staple fiber spun yarn combined and twisted, the multifilament yarn being a bulky yarn or a twisted yarn having a bulky portion on the outer periphery, and the soft polyvinyl chloride resin-impregnated coating layer containing a liquid rubber cured product. The cured liquid rubber is a polymer of one or more reactive liquid rubbers selected from the group consisting of butadiene-based, isoprene-based, and farnesene-based, and is also a composite of the reactive liquid rubber and silica particles, which is a reaction product of the reactive liquid rubber and silanol groups (Si-OH groups) on the surface of the silica particles.It is preferable that the multifilament yarn constituting the ply-twisted yarn is a factor that governs the strength, elongation, and tear strength of the canvas, and the staple spun yarn is a factor that governs the bending durability of the canvas, and in particular the amount of fluff is a factor that governs the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, i.e., the anchoring effect. In the present invention, particularly when the multifilament yarn is a bulky yarn or a twisted yarn having a bulky portion on the outer periphery, it is useful in that it combines the factors that govern the strength, elongation, and tear strength of the canvas, and the factors that govern the bending durability of the canvas and the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, as the bulky portion plays the role of fluff. The bulky multifilament yarn is a taslan-processed yarn or a woolly-processed yarn, and the twisted yarn having a bulky portion on the outer periphery is a core-spun core-sheath processed yarn, which is obtained by twisting a spun yarn around the outer periphery of the multifilament yarn. By forming a polymer alloy in which the molecular chains of the liquid rubber cured product are entangled with the vinyl chloride resin main chain within the soft polyvinyl chloride resin-impregnated coating layer, it is possible to obtain a canvas for industrial materials that has excellent flexural durability (flutter resistance) and abrasion resistance even when the soft polyvinyl chloride resin-impregnated coating layer is made lighter, and is particularly excellent in flexural durability (flutter resistance) below freezing points and joint durability (resistance to peeling at sewn parts) under the blazing sun. According to this embodiment, even if the soft polyvinyl chloride resin-impregnated coating layer is designed to be thinner than conventional products to reduce the weight of the canvas, it is possible to obtain durability equivalent to that of conventional products.

[0009] In the canvas for industrial materials of the present invention, the liquid rubber cured product is preferably a polymer of one or more reactive liquid rubbers selected from butadiene-based, isoprene-based, and farnesene-based. By forming a polymer alloy in which the molecular chains of the rubber component are entangled with the vinyl chloride resin main chain in the soft vinyl chloride resin impregnated coating layer, it is possible to obtain a canvas for industrial materials that is excellent in flexural durability (flutter resistance) and abrasion resistance even if the soft vinyl chloride resin impregnated coating layer is made lighter, and is particularly excellent in flexural durability (flutter resistance) below freezing and joint durability (difficulty in peeling off at the seams) under the blazing sun, making it possible to reduce the weight by one rank without impairing performance.

[0010] In the industrial canvas of the present invention, the liquid rubber cured product is preferably a composite with silica particles. By reacting with the silanol groups (Si-OH groups) on the surface of the silica particles and becoming part of the liquid rubber cured product, the liquid rubber cured product becomes tougher, improving its flexural durability (flutter resistance) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft polyvinyl chloride resin impregnated coating layer. This improved heat resistance not only improves the peel strength of the joint where the industrial canvases are heat-sealed and lap-jointed, but also improves the durability of the joint under the hot sun (resistance to peeling of the sewn parts), making it possible to reduce the weight by one rank without compromising performance.

[0011] The canvas for industrial materials of the present invention contains silicone fine particles in the soft polyvinyl chloride resin-impregnated coating layer, and the silicone fine particles are preferably one or more selected from silicone rubber powder, silicone resin powder, hydrophobized silica powder, grafted silicone powder, and composite powder in which the surface of silicone rubber particles is coated with silicone resin. The silicone fine particles are exposed on the surface of the soft polyvinyl chloride resin-impregnated coating layer, thereby reducing the friction coefficient of the surface of the soft polyvinyl chloride resin-impregnated coating layer, and improving the surface properties to a high lubricity, thereby significantly improving the abrasion resistance caused by dragging of the canvas, etc., and thereby enabling the extension of the service life.

[0012] The method for producing canvas for industrial materials of the present invention is a method for producing canvas composed of composite yarns of multifilament yarns / staple fiber spun yarns, in which a soft polyvinyl chloride resin-impregnated coating layer is formed on the entire surface of the fabric, comprising the steps of: 1) preparing a soft polyvinyl chloride resin composition containing at least three types of polyvinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based rubbers); 2) coating the fabric with the soft polyvinyl chloride resin composition to form a soft polyvinyl chloride resin-impregnated coating layer; (Before gelation) 3) forming a Simultaneously with the gelling heat treatment of the soft vinyl chloride resin composition to form the soft vinyl chloride resin-impregnated coating layer,The reactive liquid synthetic rubber is preferably converted into a rubber cured product to impregnate the entire soft vinyl chloride resin impregnated coating layer with a synthetic rubber component. After coating, the reactive liquid synthetic rubber molecules are present in the soft vinyl chloride resin impregnated coating layer in a state where they are entangled with the vinyl chloride resin main chain, and by curing this reactive liquid synthetic rubber, a polymer alloy in which the molecular chains of the synthetic rubber are entangled with the vinyl chloride resin main chain can be effectively formed throughout the entire soft vinyl chloride resin impregnated coating layer, resulting in an industrial canvas that is excellent in bending durability (flutter resistance) and abrasion resistance, and is particularly excellent in bending durability (flutter resistance) below freezing points and joint durability (difficulty in peeling off the stitched parts) under the blazing sun. This also makes it possible to reduce the weight by one rank without compromising performance.

[0013] In the manufacturing method of the canvas for industrial materials of the present invention, the fabric is woven from a warp yarn group and a weft yarn group, and both the warp and weft yarn groups are composed of a multifilament yarn / staple fiber spun yarn combined and twisted, and the multifilament yarn is preferably a bulky yarn or a cross-twisted yarn having a bulky portion on the outer periphery. The multifilament yarn constituting the combined and twisted yarn is an element that governs the strength, elongation, and tear strength of the canvas, and the staple fiber spun yarn is an element that governs the bending durability of the canvas, and in particular the amount of fuzz is an element that governs the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, i.e., the anchoring effect. In the present invention, particularly when the multifilament yarn is a bulky yarn or a twisted yarn having a bulky portion on the outer periphery, it is useful because it not only controls the strength, elongation, and tear strength of the canvas, but also controls the bending durability of the canvas and the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, as the bulky portion acts as fluff. The bulky yarn is a taslan-processed yarn or a woolly-processed yarn, and the twisted yarn having a bulky portion on the outer periphery is a core-spun sheath-core processed yarn, which is obtained by twisting a spun yarn around the outer periphery of the multifilament yarn.

[0014] In the manufacturing method of the canvas for industrial materials of the present invention, it is preferable to add silica particles to the soft vinyl chloride resin composition and convert it into a composite rubber cured product with the silica particles. The silanol groups (Si-OH groups) on the surface of the silica particles react with the functional groups of the reactive liquid synthetic rubber to form a synthetic rubber component / silica particle hybrid, while the molecular chains of the synthetic rubber are entangled with the vinyl chloride resin main chain to form a polymer alloy, which strengthens the soft vinyl chloride resin-impregnated coating layer, and even if the soft vinyl chloride resin-impregnated coating layer is made lighter, it maintains and sustains its bending durability (flutter resistance) and abrasion resistance, and also improves the cold resistance and heat resistance (softening temperature) of the soft vinyl chloride resin-impregnated coating layer. This improvement in heat resistance not only improves the peel strength of the joint where the industrial canvases are heat-sealed and lap-jointed, but also improves the durability of the joint under the hot sun (resistance to peeling of the sewn part). If the thermal fastness of this joint is insufficient, peeling and destruction of the joint of a tent warehouse, truck hood, etc. may occur. Effect of the Invention

[0015] The present invention provides an industrial canvas that is excellent in flexural durability (resistance to flapping) and abrasion resistance, particularly in flexural durability (resistance to flapping) below freezing points and in joint durability (resistance to peeling at seams) under the blazing sun, making it possible to reduce the weight by one rank without compromising performance. This allows for a wide range of uses as the main material for tent warehouses (simple houses), roofed tents (assembly tents with awnings attached that are used for athletic meets, outdoor events, management headquarters, meetings, receptions, etc.), truck hoods, truck bed covers, open-air storage sheets, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The canvas for industrial materials of the present invention is a fabric made of a ply-twisted yarn of multifilament yarn / staple fiber spun yarn, the multifilament yarn being a bulky yarn or a ply-twisted yarn having a bulky portion on the periphery, the soft polyvinyl chloride resin impregnated coating layer containing a cured liquid rubber (polymer of reactive liquid rubber), particularly a composite with silica particles, and further a soft polyvinyl chloride resin impregnated coating layer containing silicone microparticles. The manufacturing method of these canvas for industrial materials is as follows: 1) preparing a soft vinyl chloride resin composition containing at least three components: vinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber; 2) applying the soft vinyl chloride resin composition to a fabric to form a soft vinyl chloride resin-impregnated coating layer; and 3) converting the reactive liquid synthetic rubber into a cured rubber material to impregnate the entire soft vinyl chloride resin-impregnated coating layer with the synthetic rubber component, and further comprising a step of incorporating silica particles into the soft vinyl chloride resin composition to convert it into a cured composite rubber material with the silica particles.

[0017] The fabric used in the canvas for industrial materials of the present invention is woven from a warp yarn group and a weft yarn group, and both warp and weft yarn groups are composed of a multifilament yarn / staple fiber spun yarn combined and twisted, and the multifilament yarn is preferably a bulky yarn or a cross-twisted yarn having a bulky portion on the outer periphery (plain weave, twill weave, satin weave, twill weave, basket weave, etc.). The combined and twisted yarn of bulky multifilament yarn / staple fiber spun yarn has an anchoring effect due to the fluff of the staple fiber spun yarn and an anchoring effect with the bulky portion of the bulky multifilament yarn, which allows the soft polyvinyl chloride resin impregnated coating layer to be more firmly bonded and integrated with the surface of the fabric, resulting in excellent bending durability (resistance to fluttering) and also excellent joint durability (resistance to peeling at the sewn part). Such bulky parts can be formed by taslan processing, woolly processing, and core-spun sheath-core processing. Taslan processing is a method in which compressed air is blown onto a multifilament yarn to entangle the filaments in a loop shape to form a bulky part, woolly processing is a method in which a multifilament yarn is twisted, heat-set, and then untwisted to form a bulky part, and core-spun sheath-core processing is a method in which a multifilament long fiber yarn is used as a core and short fiber staples are twisted all around it to form a bulky part of a pseudo-short fiber spun yarn having a core-sheath structure with a mass ratio of 10:1 to 2:1. All of these bulky yarns have the strength (tear resistance) of multifilament (long fiber yarn), but have hooks (fluff or loose bulk) equivalent to the fluff of staple spun yarn, which gives them the advantage of providing an anchoring effect to the soft polyvinyl chloride resin-impregnated coating layer, and the soft polyvinyl chloride resin-impregnated coating layer that covers the bulky yarn provides the diffuse reflective portion of the canvas's appearance.

[0018] The fiber types of the multifilament yarn (bulky) and the staple spun yarn include synthetic fibers (various polymers, recycled polymers), natural fibers (cotton, kenaf, etc., used for staple spun yarn), semi-synthetic fibers (rayon), and inorganic fibers (glass fibers, carbon fibers, etc.). In particular, synthetic fibers such as polypropylene fibers, polyethylene fibers, vinylon fibers, polyester fibers, nylon fibers, acrylic fibers, and polyurethane fibers are preferred from the perspective of the balance between versatility and physical properties, and polyester fibers (particularly polyethylene terephthalate, and furthermore, recycled polyethylene terephthalate obtained by depolymerizing recycled polyethylene terephthalate and polymerizing the recycled monomer), nylon fibers, and vinylon fibers are particularly preferred. In particular, in order to dramatically improve the tear resistance of the fabric, high-strength multifilament yarns of wholly aromatic polyester fibers (polyarrelate), wholly aromatic polyamide fibers (aramid), and aromatic heterocyclic polymer fibers (polybenzoxazole, polybenzimidazole, polybenzothiazole, etc.) can be used. Furthermore, in a fabric (woven material) using a multifilament yarn of polyester fiber, a ripstop fabric designed by replacing the multifilament yarn at specific intervals in the warp yarn group and the weft yarn group with the above-mentioned high-strength multifilament yarn can also be used. In a core-spun yarn, which is a core-sheath yarn having a bulky portion on the outer periphery, the fiber type of the staple fiber used for the sheath is preferably the same as that of the core, but a different combination of, for example, a multifilament yarn of wholly aromatic polyamide fiber (aramid) for the core and a polyester staple fiber for the sheath may also be used.

[0019] Multifilament yarns (bulk) can be of general-purpose fineness such as 250 denier, 500 denier, 750 denier, 1000 denier, and 1250 denier (278 dtex, 555 dtex, 833 dtex, 1111 dtex, and 1388 dtex), and are particularly preferably 500 denier, 750 denier, and 1000 denier (555 dtex, 833 dtex, and 1111 dtex), but are not limited to multiples of 250 denier. The filament single yarn of the multifilament yarn is 3 to 10 denier, preferably 4 to 6 denier, and for example, the number of filaments of a 500 denier yarn is about 50 to 166 (preferably about 83 to 125), and the larger the fineness number, the higher the strength (breaking strength, tear strength). The number of twists of the yarn is preferably 10 to 200 times / m, and more preferably 20 to 100 times / m. If the number of turns exceeds 200 / m, the bulky part will be wound tightly, impairing the anchor effect on the soft polyvinyl chloride resin-impregnated coating layer. As for the staple spun yarn, the following cotton counts may be used: 10-count single yarn (590 dtex), 14-count single yarn (422 dtex), 15-count single yarn (394 dtex), 20-count single yarn (295 dtex), and 30-count single yarn (197 dtex), with 14-count single yarn, 15-count single yarn, and 20-count single yarn being particularly preferred. Also, 14-count two-ply yarn (844 dtex), 15-count two-ply yarn (788 dtex), 20-count two-ply yarn (590 dtex), and 30-count two-ply yarn (394 dtex), with 20-count two-ply yarn and 30-count two-ply yarn being particularly preferred. The smaller the count number, the higher the strength (breaking strength, tear strength). These are twisted yarns (doubled yarns, plied yarns) with 100 to 1,000 twists / m and a twist factor of 3.0 to 4.5, either S (right) twist or Z (left) twist.

[0020] Specifically, the multifilament yarn (bulky) / staple fiber spun yarn twisted yarn is classified into the following types: "278dtex / 30 count single yarn", "278dtex / 20 count single yarn", "278dtex / 15 count single yarn", "555dtex / 20 count two-ply yarn", "555dtex / 10 count single yarn", "555dtex / 14 count single yarn", "833dtex / 14 count two-ply yarn", "833dtex / 15 count two-ply yarn", "833dtex / 20 ... "2-ply yarn", "1111dtex / 14-ply yarn", "1111dtex / 15-ply yarn", "1111dtex / 20-ply yarn", "278dtex / 278dtex / 20-ply yarn", "278dtex / 278dtex / 30-ply yarn", "278dtex / 555dtex / 14-ply yarn", "278dtex / 555dtex / 15-ply yarn", "278dtex / 555dtex / 20-ply yarn" , "555dtex / 555dtex / 14 count single yarn", "555dtex / 555dtex / 15 count single yarn", "555dtex / 555dtex / 20 count double yarn", "555dtex / 30 count single yarn / 30 count single yarn", "555dtex / 20 count single yarn / 30 count single yarn", "555dtex / 20 count single yarn / 20 count single yarn", "833dtex / 14 count single yarn / 14 count single yarn", "833dtex / 14 The number of ply-twisted yarns (two-ply yarns are counted as one) is preferably two or three, and the number of ply-twisted turns is 100 to 500 turns / m, preferably 150 to 300 turns / m, such as "1111 dtex / 15 count single yarn / 15 count single yarn", "1111 dtex / 10 count single yarn / 10 count single yarn", "1111 dtex / 10 count single yarn / 14 count single yarn", and "1111 dtex / 14 count single yarn / 14 count single yarn". The more the number of ply-twisted turns exceeds 500 turns / m, the tighter the yarn winding becomes, and the bulky part of the bulky multifilament yarn disappears, tending to impair the anchoring effect. The weave density of the twisted yarn (multifilament yarn / staple fiber spun yarn) is 25 to 55 warp threads, preferably 30 to 46 warp threads, and 28 to 58 weft threads, preferably 34 to 50 weft threads per inch. The void ratio is 0 to 15% and the fabric (plain weave, twill weave, satin weave, twill weave, basket weave, etc.) is suitable. The mass of the fabric is 170 g / m 2 ~410g / m 2 , preferably 190 g / m 2~260g / m 2 It is.

[0021] The fabric used may have been subjected to known fiber treatments such as scouring, bleaching, dyeing, softening, water repellency, waterproofing, flame retardancy, and calendaring. If the soft polyvinyl chloride resin-impregnated coating layer of the canvas is damaged by scratches, wear, cracks, or other damage, rainwater may seep in through the damaged area, causing water leakage problems. To prevent water leakage, the entire fabric is impregnated with a water repellent (0.3 to 6 g / m2). 2 ) to prevent water absorption. The water repellent is an emulsion of a perfluoroalkyl group-containing copolymer resin made by using an ethylenically unsaturated monomer having a perfluoroalkyl group or a perfluoroalkenyl group having 8 or less carbon atoms. Specifically, it is a copolymer of an acrylate and / or methacrylate having a perfluoroalkyl group having 8 or less carbon atoms and a monomer such as (meth)acrylic acid, (meth)acrylic acid ester, (meth)acrylamide, maleic acid or phthalic acid alkyl ester, vinyl chloride, vinylidene chloride, ethylene, or styrene. These water repellents obtain a high degree of water repellency by orienting and aligning the perfluoroalkyl group by thermal curing at 120 to 180°C. Other water repellents include silicone-based water repellents such as methylchlorosilane, methylpolysiloxane resin, dimethylpolysiloxane, and methylhydrogenpolysiloxane, paraffin-based water repellents such as n-paraffin wax with 20 to 48 carbon atoms and a melting point of 50 to 70°C, complexes of these paraffin-based compounds with zirconium, and other compounds such as alkylene urea compounds (octadecylethylene urea), aliphatic amide compounds (N-methylolstearylamide), polyvinylpyrrolidone, and water-absorbent resins (which suppress capillary action by swelling with water retention), such as sodium polyacrylate (crosslinked), carboxymethylcellulose crosslinked, and polyvinyl alcohol crosslinked. Water absorption prevention treatment can be performed by using different types of water repellents and forming two water-repellent layers, one on the inside and one on the outside, through two impregnation steps, or by forming a two-type mixed water-repellent layer through one impregnation step. The method of forming two water-repellent layers, inner and outer, is to temporarily form the inner layer by only drying treatment after the first impregnation, and then to perform thermal curing at 130 to 180°C all at once after the second impregnation and drying.

[0022] The soft vinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric is formed by coating and heat treatment gelation of a soft vinyl chloride resin composition, or by dipping and heat treatment gelation. Here, the vinyl chloride resin refers to vinyl chloride resin, crosslinked vinyl chloride resin, chlorinated vinyl chloride resin, ethylene-vinyl chloride copolymer, vinyl acetate-vinyl chloride copolymer, acrylic-(graft)vinyl chloride copolymer, urethane-vinyl chloride (graft) copolymer, etc. The soft vinyl chloride resin composition is a liquid paste sol containing at least three types of vinyl chloride resin, plasticizer, and liquid synthetic rubber. Specifically, the soft polyvinyl chloride resin composition mainly contains a paste polyvinyl chloride resin (emulsion polymerization type, preferably a biomass synthetic product) having a number average molecular weight of 1000 to 2000, 40 to 100 parts by mass of a plasticizer (adipic acid ester compound, a phthalate ester compound, a cyclohexane dicarboxylate ester compound, a cyclohexene dicarboxylate ester compound, a phosphate ester compound, a chlorinated paraffin compound, a polyester compound, or the like, preferably a biomass synthetic product) relative to 100 parts by mass of the paste polyvinyl chloride resin, and 5 to 30 parts by mass of a liquid synthetic rubber (butadiene rubber, isoprene rubber, farnesene rubber, or the like, preferably a biomass synthetic product, which is later converted into a rubber cured product) relative to 100 parts by mass of the paste polyvinyl chloride resin.Other compounding agents include stabilizers (barium-zinc complexes, calcium-zinc complexes, epoxidized soybean oil, etc.), flame retardants (antimony trioxide, antimony pentoxide, aluminum hydroxide, magnesium hydroxide, zinc borate, etc.), fillers (calcium carbonate, barium sulfate, talc, etc.), UV resistance agents (benzophenone tautomers, benzotriazole tautomers, triazine tautomers, hindered amine compounds, etc.), adhesives (multifunctional isocyanate compounds, silane coupling agents, etc.), and mold inhibitors (imidazoles). Preferred are blended compositions containing any and any amounts of compounds such as ethylhexyl ether compounds, thiazole compounds, isothiazolinone compounds, pyridine compounds, N-haloalkylthio compounds, phenoxyarsine compounds, etc., pigments (titanium oxide, carbon black, inorganic compounds, azo compounds, phthalocyanine compounds, anthraquinone compounds, quinacridone compounds, etc.), to which known additives such as fluorescent whitening agents, antistatic agents, surfactants, antioxidants, chemical foaming agents, insect repellents, deodorants, and heat-shielding pigments can be added as necessary.

[0023] The reactive liquid synthetic rubber is one or more selected from butadiene rubber, isoprene rubber, and farnesene rubber, and is used in the range of 5 to 30 parts by mass per 100 parts by mass of the paste vinyl chloride resin. The reactive liquid synthetic rubber is compatible with the plasticizer contained in the soft vinyl chloride resin composition, and penetrates into the vinyl chloride resin fine particles together with the plasticizer to become a softener for the vinyl chloride resin. In this state, the soft vinyl chloride resin composition is heated and gelled to form a soft vinyl chloride resin impregnated coating layer. In the soft vinyl chloride resin impregnated coating layer after coating, the reactive liquid synthetic rubber molecules are entangled with the vinyl chloride resin main chain. Next, the reactive liquid synthetic rubber is cured to enable hybrid formation in which a network of rubber molecular chains is entangled with the vinyl chloride resin main chain throughout the entire soft vinyl chloride resin impregnated coating layer. The integration of the vinyl chloride resin with the cured liquid rubber makes the soft vinyl chloride resin impregnated coating layer strong, improving resistance to bending, wear, heat and cold.

[0024] The reactive butadiene liquid rubber forms a rubber cured product by having either a -COOH group or a -OH group at the molecular end. The molecular weight Mn is preferably 1000 to 5000, particularly 1300 to 3500, and the viscosity is preferably in the range of 50 to 1000 poise (25°C), particularly 200 to 500 poise (25°C). The reactive butadiene liquid rubber contains 5 to 25% by mass of styrene and / or acrylonitrile as a block copolymerization component, and 10 to 50% by mass of isoprene or hydrogenated isoprene as a copolymerization component. The reactive butadiene liquid rubber has low viscosity and excellent rubber elasticity when rubberized when it has about 75 to 80% of 1,4-cis structure or 1,4-trans structure and about 20 to 25% of 1,2-vinyl structure. This generation ratio is possible by a radical polymerization method. The reactive isoprene liquid rubber preferably has either a -COOH group or a -OH group at the molecular (both) terminals and has a molecular weight Mn in the range of 3000 to 25000. The reactive isoprene liquid rubber contains 5 to 25 mass% of styrene and / or acrylonitrile as a block copolymerization component, and 10 to 50 mass% of butadiene or hydrogenated isoprene as a copolymerization component. Examples of reactive farnesene rubber include rubbers containing α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecatetraene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecatriene) as monomers, copolymer rubbers of farnesene and styrene, and copolymer rubbers of farnesene and butadiene. The reactive Funnelsen liquid rubber preferably has either a -COOH group or a -OH group at the molecular (both) terminals and has a molecular weight Mn in the range of 3000 to 50000. The cured products of these liquid synthetic rubbers are formed by dehydration condensation of the -COOH group and -OH group at the molecular (both) terminals, but can also be formed by addition reaction with crosslinking agents such as diamines, polyamines, diisocyanates, polyisocyanates, epoxy-amines, aziridines, and oxazolines, or condensation reaction with compounds such as diols, polyols, dicarboxylic acids, and polycarboxylic acids.

[0025] Furthermore, a rubber cured product in which part of the liquid rubber cured product is bonded to silica particles can also be used. By reacting with the silanol groups (Si-OH groups) on the surface of the silica particles and becoming part of the liquid rubber cured product, the liquid rubber cured product becomes tougher, improving its flexural durability (resistance to flapping) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft polyvinyl chloride resin impregnated coating layer. This improved heat resistance not only improves the peel strength of the joint when industrial canvases are joined together with a heat-sealed lap, but also improves the durability of the joint under the hot sun (resistance to peeling of the sewn parts). Silica particles are used in an amount of 1 to 25% by weight with respect to the liquid synthetic rubber, and are incorporated as part of the rubber hardened product by forming (dehydration condensation) chemical bonds between the silanol groups (Si-OH groups) on the silica surface and the -COOH and -OH groups at the molecular (both) ends of the reactive liquid synthetic rubber, so that the silica particles are contained in an amount of 0.05 to 2.5% by mass with respect to the soft polyvinyl chloride resin impregnated coating layer. Furthermore, by adding a crosslinking agent such as diamine, polyamine, diisocyanate, polyisocyanate, epoxy-amine, aziridine, oxazoline, or by intervening a compound such as diol, polyol, dicarboxylic acid, polycarboxylic acid, the molecular chain can be lengthened to improve the flexibility and toughness of the rubber hardened product. The generation of such a rubber hardened product is carried out simultaneously with the gelation heat treatment of the soft polyvinyl chloride resin paste that forms the soft polyvinyl chloride resin impregnated coating layer, and a homogeneous rubber hardened product is formed throughout the soft polyvinyl chloride resin impregnated coating layer. The soft polyvinyl chloride resin paste composition may contain a silane coupling agent to assist the chemical bonding between the liquid synthetic rubber and the silica.

[0026] Silica has a BET specific surface area of ​​100 to 300 m 2Synthetic amorphous silica having a particle size of 1 to 40 μm or less is preferred. Synthetic amorphous silica may be either wet-process silica (precipitation method or gel method) or dry-process silica (fumed silica). The surface of the silica has silanol (Si-OH group), and the silanol group reacts with -COOH group, -OH group, etc. at the molecular (both) ends of reactive liquid synthetic rubber, and the silica particles become part of the rubber component. In particular, this reaction is subjected to an addition reaction with a crosslinking agent such as diamine, polyamine, diisocyanate, polyisocyanate, epoxy-amine, aziridine, oxazoline, or a compound such as diol, polyol, dicarboxylic acid, polycarboxylic acid, etc., to toughen the rubber cured product, improving its bending durability (flutter resistance) and abrasion resistance, and also improving the cold resistance and heat resistance (softening temperature) of the soft vinyl chloride resin impregnated coating layer. This improved heat resistance is not only improved in peel strength at the joint where industrial canvases are heat-sealed and lap-bonded, but also manifests itself as peel resistance at surface temperatures of 40 to 60°C under the blazing sun. Functional groups such as amino groups, vinyl groups, epoxy groups, methacryl groups, acrylic groups, chlorine groups, mercapto groups, isocyanurate groups, and isocyanate groups may be introduced onto the silica surface. The silica particles are preferably surface-modified particles treated with a silane coupling agent. Silane coupling agents are alkoxysilane compounds having two or more different reactive groups in the molecule represented by the general formula: XR-Si(Y)3, for example, X=amino group (aminosilane), vinyl group (vinylsilane), epoxy group (epoxysilane), methacryl group (methacrylsilane), acrylic group (acrylicsilane), chloro group (chlorosilane), mercapto group (mercaptosilane), isocyanurate group (isocyanuratesilane), isocyanate group (isocyanatesilane), etc. (R=alkyl chain), Y=methoxy group, ethoxy group, etc. Surface modification of silica is -Si-R-Si(Y)3 modification of the silanol group of silica, but it may also be (-O)3Si-RX modification of the siloxane bond part of silica.

[0027] In order to improve the abrasion resistance of the soft polyvinyl chloride resin-impregnated coating layer and extend the service life of the synthetic canvas, it is preferable that the soft polyvinyl chloride resin-impregnated coating layer contains 0.05 to 5.0 mass % of silicone fine particles, and the silicone fine particles are preferably one or more selected from silicone rubber powder, silicone resin powder, hydrophobic silica powder, grafted silicone powder, and composite powder in which the surface of silicone rubber particles is coated with silicone resin. The silicone rubber powder is a spherical fine powder (average particle size 5 to 13 μm) or irregular particles (average particle size 25 to 140 μm) of silicone rubber crosslinked with linear dimethylpolysiloxane, and the silicone resin powder is a silicone rubber having a siloxane bond (RSiO 3 / 2 The hydrophobic silica powder is spherical particles (average particle diameter 0.8-3.5 μm) of spherical amorphous silica whose surface is hydrophobized with silicone. The grafted silicone powder is spherical particles (average particle diameter 20-30 μm, silicone content 70-90% by mass) of graft polymer in which acrylic side chains or vinyl acetate side chains are introduced to linear organopolysiloxane. The composite powder in which the surface of silicone rubber particles is coated with silicone resin is spherical fine powder of silicone rubber crosslinked with linear dimethylpolysiloxane whose surface is hydrophobized with siloxane bonds (RSiO 3 / 2 The spherical composite particles (average particle diameter: 5 to 12 μm) are coated with a polyorganosilsesquioxane cured product crosslinked in a three-dimensional network represented by n, where R is a monovalent organic group, n is an integer of 1000 or more, and examples of the organic group R include alkyl groups such as methyl, ethyl, propyl, isopropyl, and butyl groups, aryl groups such as phenyl and tolyl groups, alkenyl groups such as vinyl and allyl groups, 3,3,3-trifluoropropyl groups, γ-mercaptopropyl groups, γ-glycidoxypropyl groups, γ-methacryloxypropyl groups, and γ-aminopropyl groups.

[0028] The following lubricants can be used in combination with these silicone microparticles, and the lubricating effect of the lubricant further reduces the friction coefficient of the soft polyvinyl chloride resin-impregnated coating layer, thereby reducing wear and extending the service life. The lubricants are preferably hydrocarbon-based (low molecular weight polyethylene, paraffin), fatty acid-based (stearic acid, hydroxystearic acid, complex stearic acid, oleic acid), aliphatic alcohol-based, aliphatic amide-based (stearamide, oxystearamide, oleylamide, erucylamide, ricinoleamide, behenamide, methylolamide, methylene bisstearamide, methylene bisstearbehenamide, bisamic acid of higher fatty acid, stearamide, complex amide), aliphatic ester-based (n-butyl stearate, methylhydroxystearate, polyhydric alcohol fatty acid ester, saturated fatty acid ester, ester wax), fatty acid metal soap-based, silicone oil, etc., used alone or in combination at 10 to 50% by mass relative to the silicone microparticles.

[0029] The manufacturing method of canvas for industrial materials of the present invention, in which canvas is composed of a composite yarn of multifilament yarn / short fiber spun yarn and has a soft polyvinyl chloride resin-impregnated coating layer formed on the entire surface of the fabric, is characterized by including the following steps: 1) preparing a soft polyvinyl chloride resin composition containing at least three types of vinyl chloride resin, plasticizer, and reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based), 2) applying the soft polyvinyl chloride resin composition to the fabric to form a soft polyvinyl chloride resin-impregnated coating layer, and 3) converting the reactive liquid synthetic rubber into a cured rubber product to impregnate the entire soft polyvinyl chloride resin-impregnated coating layer with synthetic rubber components. Coating of the soft vinyl chloride resin composition (paste sol) onto the fabric and formation of the soft vinyl chloride resin impregnated coating layer can be carried out by dipping (immersion-impregnation-roll squeezing-heat treatment gelation of the paste sol) or coating (impregnation coating-heat treatment gelation of the paste sol) such as gravure coating method, comma coating method, roll coating method, reverse roll coating method, bar coating method, doctor knife coating method, etc. To convert liquid synthetic rubber into a rubber cured product, a crosslinking agent such as diamine, triamine, tetramine, polyamine, diisocyanate (e.g., hexamethylene diisocyanate: HMDI), triisocyanate (e.g., isocyanurate by trimer of HMDI), polyisocyanate, epoxy-amine, aziridine, oxazoline, etc., especially a crosslinking agent with 3 or 4 functional groups, is used to make a dense and complex rubber cured product. The conversion of the liquid synthetic rubber into a rubber hardened product is carried out simultaneously with the gelation of the soft vinyl chloride resin composition, so that a homogeneous rubber hardened product is formed throughout the soft vinyl chloride resin impregnated coating layer. The reaction between the liquid synthetic rubber and the crosslinking agent is preferably an equimolar reaction, but excess liquid synthetic rubber may remain in the soft vinyl chloride resin impregnated coating layer. The remaining liquid synthetic rubber is compatible with the plasticizer and acts to lower the glass transition temperature of the soft vinyl chloride resin impregnated coating layer, that is, as an agent that imparts cold resistance. The remaining liquid synthetic rubber is 1 to 10 parts by mass per 100 parts by mass of the vinyl chloride resin.

[0030] The soft polyvinyl chloride resin impregnated coating layer is 200 to 400 g / m 2The lower the weight, the lighter the canvas will be, and the higher the weight, the stronger the canvas will be and the longer its durability (service life). Conventional canvas for industrial materials is No. 2 (approx. 410 g / m 2 ), No. 3 (approximately 340g / m 2 ), No. 4 (approximately 280g / m 2 ), No. 5 (approximately 250g / m 2 ), No. 6 (approximately 200g / m 2 ) and No. 7 (approx. 170g / m 2 ) fabric as the base fabric, with a soft vinyl chloride resin impregnated coating layer, and No. 2 canvas (approx. 750 g / m 2 ), No. 3 canvas (approx. 640g / m 2 ), No. 4 canvas (approx. 560g / m 2 ), No. 5 canvas (approx. 530g / m 2 ), No. 6 canvas (approx. 470g / m 2 ), No. 7 canvas (approx. 430g / m 2 However, in the case of the canvas for industrial materials of the present invention, even if a fabric one rank lighter is used, sufficient tear strength can be obtained, for example, about 530 g / m 2 No. 4 canvas, approx. 470g / m 2 No. 5 canvas, approx. 430g / m 2 No. 6 canvas, approx. 390g / m 2 This makes it possible to make the canvas one level lighter, similar to No. 7 canvas.

[0031] The canvas for industrial materials of the present invention may also be provided with an antifouling layer, which may be, for example, a transparent layer made of an acrylic resin, a fluorine-based copolymer resin, an acrylic-silicone copolymer resin, an acrylic-fluorine copolymer resin, an acrylic-urethane copolymer resin, a blend of an acrylic resin and a fluorine-based copolymer resin, or a layer containing silica particles, colloidal silica, an organosilicate, a silane coupling agent, an ultraviolet absorber (benzophenone tautomer, benzotriazole tautomer, triazine tautomer, etc.) in these resins. These antifouling layers are formed by applying and drying these coating materials using gravure coating, or by laminating a fluorine-containing resin film or a multilayer film such as a fluorine-containing resin / acrylic resin layer with an adhesive or by thermal melting. In addition, a photocatalytic layer containing a photocatalytic inorganic material (for example, photocatalytic titanium oxide, photocatalytic tungsten oxide, etc.) on these antifouling layers may also be provided.

[0032] The manufacturing process of the canvas for industrial materials of the present invention may include a step of applying surface decorative embossing. Surface decorative embossing can be performed by known embossing methods, such as glossing with a mirror roll, matte finish with a matte finish roll, and design with a pattern roll. In particular, it is preferable to apply an identification mark of the manufacturer's name (e.g., "HIRAOKA"), logo mark, or product name (e.g., "ULTRA MAX") at specific intervals (e.g., every 100 cm) to the end or specific parts of the canvas for industrial materials. Such identification markings include a design in which the entire canvas is matte embossed and only the identification marking part is mirror embossed, or a design in which the entire canvas is mirror embossed and only the identification marking part is matte embossed, or an embossing in which the identification marking part is recessed, and these markings make it easy to distinguish from similar products of other companies. The embossing is performed by pressing an embossing roll set at 100 to 180°C with a pair of rubber rolls, and the embossing is fixed by cooling (air-cooled and water-cooled rolls) after embossing.

[0033] The present invention will now be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the scope of these examples. The test methods used in the examples and comparative examples of the present invention are as follows. (1) Tear strength (N: JIS L1096 A-1 single tongue method) (2) Scott type reciprocating bending abrasion test (JIS L1096 8.19.2 B method) Test pieces measuring 25mm wide x 120mm long were taken from the canvas and left to stand in a 25°C environment for 24 hours. Then, they were attached to a Scott-type testing machine and subjected to 1,000 and 3,000 reciprocating flexions with a load of 1kgf in a constant temperature room at 25°C. After the test, the surface condition was observed and the dynamic cold resistance was judged as follows: 1: Minor wear is observed 2: Wear marks are observed on the soft polyvinyl chloride resin impregnated coating layer, but there is no problem. 3: The soft polyvinyl chloride resin impregnated coating layer peels off or wears away, exposing the fabric (Less than 10%) 4: The soft polyvinyl chloride resin impregnated coating layer peels off or is worn away, exposing the fabric Accept (more than 10%) (3) Scott type reciprocating bending abrasion test (JIS L1096 8.19.2 B method) Test pieces measuring 25mm wide x 120mm long were taken from the canvas and left to stand in a -10°C environment for 24 hours. They were then attached to a Scott-type testing machine and subjected to 100 and 300 reciprocating flexions with a load of 1kgf in a constant temperature room at -10°C. The surface condition after the test was observed and the dynamic cold resistance was judged as follows: 1: No abnormality is detected 2: Minor cracks observed in the soft polyvinyl chloride resin impregnated coating layer 3: Peeling or falling off of the soft polyvinyl chloride resin impregnated coating layer is observed. (4) Dematcha repeated bending fatigue durability test (JIS K6301 compliant) A 50mm wide x 150mm long sample was taken from the canvas and left to rest in a -10℃ environment for 24 hours, after which it was folded in half top and bottom from the 25mm centre of the width to create a 25mm wide x 150mm long folded test piece. This was then attached to a YSS Dematcha Flexing Tester (manufactured by Yasuda Seiki Mfg. Co., Ltd.) and a simulated test of repeatedly folding and unfolding the test piece was carried out 100 and 300 times in a constant temperature room at -10℃, and the surface condition of the test piece was observed to determine the dynamic cold resistance as follows. 1: No abnormality is detected 2: Minor cracks observed in the soft polyvinyl chloride resin impregnated coating layer 3: Partial peeling or falling off of the soft polyvinyl chloride resin impregnated coating layer is observed. (5) Heat resistance creep test of joints (heat resistance test) The ends of the two pieces of canvas in the weft direction were overlapped in a straight line with a width of 8 cm, and the soft polyvinyl chloride resin impregnated coating layer was melted by oscillation at an anode current of 1.0 A using a high-frequency welder (YAMAMOTO VINITA Co., Ltd. YTO-8A type: high-frequency output 8KW) equipped with a 4 cm wide x 30 cm long weld bar (flat blade) to obtain a canvas joint. A test piece of 3 cm wide x 30 cm long (warp direction) was taken from this joint, overlapping the fused joint and including a width of 8 cm in the warp direction, and used as a creep resistance test piece. The heat creep resistance in the warp direction was evaluated using a creep tester (TOYO SEIKI SEISAKUSHO Co., Ltd.: 100LDR type) under conditions of 25°C x 24 hours and load conditions of 50 kgf, 60 kgf, and 70 kgf. Similarly, a test piece in the weft direction was prepared and the heat creep resistance in the weft direction was evaluated. Evaluation criteria 1: After 24 hours, some stretching was observed at the joint (Excellent) 2: The joint broke and the test piece broke apart within 12 to 24 hours (good). 3: The joint broke and the test piece broke apart within 1 to 12 hours (poor) 4: The joint broke and the test piece broke apart within 1 hour (failure)

[0034] Example 1 <Fabric (1)> The warp and weft yarns are made of polyester 555 dtex (96 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 20-count two-ply yarn (590 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns have a thread density of 33 threads / inch and the weft yarns have a thread density of 30 threads / inch. The void ratio is 8% and the mass is 215 g / m. 2 The fabric used was: The fabric was treated for water repellency (dipping, heat treatment) with an acrylate / vinyl chloride resin copolymer emulsion (solid content 5% by mass) having a perfluoroalkyl group with 6 carbon atoms to prevent rainwater penetration (water absorption) in the event that an abnormality occurs in the soft vinyl chloride resin impregnated coating layer. This was designated fabric (1). <Soft polyvinyl chloride resin impregnated coating layer> A processing liquid was prepared based on a vinyl chloride resin composition paste (vinyl chloride resin, plasticizer, butadiene-based liquid rubber) for forming a soft vinyl chloride resin-impregnated coating layer of the following <Composition 1>. Next, the fabric (1) was dipped (immersed) in a liquid bath filled with this processing liquid, and the processing liquid of <Composition 1> was impregnated into the fabric (1) at normal pressure. The fabric (1) was then pulled out of the liquid bath and simultaneously squeezed with a rubber mangle roll to remove excess processing liquid, forming a soft vinyl chloride resin-impregnated coating layer. Next, a gelation heat treatment was performed for 3 minutes in a hot air oven at 180°C to form a soft vinyl chloride resin-impregnated coating layer of 255 g / m 2 is formed on the entire surface of the fabric (1), with a mass of 470 g / m 2 This gelling heat treatment converts the polyvinyl chloride resin composition paste into soft polyvinyl chloride resin and at the same time converts the butadiene-based liquid rubber into hardened rubber, forming a polymer alloy in which the molecular chains of the hardened rubber are entangled with the polyvinyl chloride resin main chain throughout the entire area of ​​the soft polyvinyl chloride resin-impregnated coating layer obtained. <Formulation 1> Processing fluid for forming soft polyvinyl chloride resin impregnated coating layer Paste polyvinyl chloride resin (degree of polymerization 1700) 100 parts by weight Diisononyl phthalate (DINP plasticizer) 60 parts by weight Butadiene-based liquid rubber* 10 parts by mass Isocyanurate (HMDI* trimer: NCO crosslinking agent) 2 parts by weight Chlorinated paraffin (flame retardant and plasticizer) 5 parts by weight Epoxidized soybean oil (stabilizer and plasticizer) 4 parts by weight Antimony trioxide (flame retardant) 20 parts by weight Zinc stearate (stabilizer) 2 parts by weight UV absorber (triazine tautomer) 0.5 parts by weight Titanium oxide (white pigment) 1 part by weight Phthalocyanine green (green pigment) 3 parts by weight Carbon black (black pigment) 0.5 parts by weight Silicone resin powder (lubricant: average particle size 2 μm) 4 parts by weight Trichloroethylene (dilution solvent) 20 parts by weight *Butadiene liquid rubber: Contains 15% by mass of styrene as a block copolymer component. Properties: Average molecular weight 3000 with -COOH groups at both ends of the molecule *HMDI: Hexamethylene diisocyanate HMDI trimer (isocyanurate) has three isocyanate groups

[0035] Example 2 The fabric (1) in Example 1 was changed to fabric (2) and blend 1 was changed to blend 2, but the same as in Example 1, with a mass of 470 g / m 2 Obtained Canvas (2). In <Mixture 2>, 10 parts by mass of the butadiene liquid rubber in <Mixture 1> has been replaced with 10 parts by mass of isoprene liquid rubber. The isoprene liquid rubber contains 10% by mass of acrylonitrile as a block copolymer component, has -COOH groups at both ends of the molecule, and has an average molecular weight of 2500. In addition, 2 parts by mass of surface-modified silica particles have been added. These surface-modified silica particles are dry silica (gel method: average particle size 2 μm, BET specific surface area 300 m 2 / g) was stirred at 24°C for 3 hours in a 5% by mass aqueous solution of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (silane coupling agent), separated and dried, and contains a mixture of -Si-R-Si(OCH3)3 modifications that bond to the silanol groups of the silica and (-O)3Si-R-NH2 modifications that bond to the siloxane moieties.Furthermore, 4 parts by mass of silicone resin powder was replaced with 4 parts by mass of composite powder (average particle size 6μm) in which the surfaces of silicone rubber particles are coated with silicone resin. <Fabric (2)> The warp and weft yarns are made of polyester 555 dtex (96 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 10 count single yarn (590 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns have a pick density of 33 threads / inch and the weft yarns have a pick density of 30 threads / inch. The void ratio is 8% and the mass is 215 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0036] Example 3 The fabric (1) in Example 1 was changed to fabric (3) and blend 1 was changed to blend 3, but the same as in Example 1 was used. The mass was 462 g / m 2 Obtained Canvas (3). In <Mixture 3>, 10 parts by mass of the butadiene liquid rubber in <Mixture 1> is replaced with 10 parts by mass of β-funnelsen liquid rubber, which contains 10% by mass of butadiene as a block copolymer component, has -COOH groups at both molecular ends, and has an average molecular weight of 5000. In addition, 4 parts by mass of silicone resin powder is replaced with 4 parts by mass of spherical particles (average particle size 30 μm) made of a graft polymer (silicone content 70% by mass) in which an acrylic side chain has been introduced into linear dimethylpolysiloxane. <Fabric (3)> The warp and weft yarns were made of polyester 555 dtex (96 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 14 count single yarn (422 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns had a thread density of 33 threads / inch and the weft yarns had a thread density of 30 threads / inch. The void ratio was 11% and the mass was 208 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0037] Example 4 The fabric (1) in Example 1 was changed to fabric (4), and the fabric was the same as Example 1, with a mass of 483 g / m 2 Obtained Canvas (4). <Fabric (4)> The warp and weft yarns are made of polyester 833 dtex (144 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 14-count two-ply yarn (844 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns have a thread density of 30 threads / inch and the weft yarns have a thread density of 27 threads / inch. The void ratio is 4% and the mass is 228 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0038] Example 5 The fabric (2) in Example 2 was changed to fabric (5), and the mass was 502 g / m. 2 Obtained Canvas (5). <Fabric (5)> The warp and weft yarns were made of polyester 833 dtex (144 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 15-count two-ply yarn (788 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns had a thread density of 30 threads / inch and the weft yarns had a thread density of 27 threads / inch. The void ratio was 8% and the mass was 213 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0039] Example 6 The fabric (3) in Example 3 was changed to fabric (6), but the fabric was the same as in Example 3, with a mass of 490 g / m 2 of Canvas (6). <Fabric (6)> The warp and weft yarns are made of polyester 833 dtex (144 filaments) multifilament yarn (20 twists / m taslan processed yarn) and polyester 20 count two-ply yarn (590 dtex: 200 twists / m) staple spun yarn (125 twists / m). The warp yarns have a thread density of 33 threads / inch and the weft yarns have a thread density of 30 threads / inch. The void ratio is 8%, and the mass is 198 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0040] Example 7 The fabric (1) in Example 1 was changed to fabric (7), but the fabric was the same as Example 1, with a mass of 473 g / m 2 of Canvas (7). <Fabric (7)> The warp and weft yarns are made of a polyester 555 dtex (96 filaments) multifilament yarn (twist count 100 times / m) as the core, and the entire circumference is covered with 1.4 denier (1.56 dtex) short fiber polyester staple with a length of 100 mm to give a core / sheath ratio of 70 / 30 by mass. The core spun core-sheath yarn and polyester 20-count two-ply (590 dtex) short fiber spun yarn are used to make a twisted yarn (twist count 125 times / m). The warp yarn density is 30 threads / inch and the weft yarn density is 27 threads / inch. The yarn is plain woven with a void ratio of 8% and a mass of 216 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0041] Example 8 The fabric (2) in Example 2 was changed to fabric (8), but the fabric was the same as Example 2, with a mass of 473 g / m 2 The result was Canvas (8). <Fabric (8)> The warp and weft yarns are made of a polyester 555 dtex (96 filaments) multifilament yarn (twist count 100 times / m) as the core, and the entire circumference is covered with 1.4 denier (1.56 dtex) short fiber polyester staple with a length of 100 mm to give a core / sheath ratio of 70 / 30 by mass. The core spun core-sheath yarn and polyester 10-count single yarn (590 dtex) short fiber spun yarn are used to make a twisted yarn (twist count 125 times / m). The warp yarn density is 30 threads / inch and the weft yarn density is 27 threads / inch. The yarn is plain woven with a void ratio of 8% and a mass of 216 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used.

[0042] [Examples 9 to 16] The surfaces of the canvases (1) to (8) of Examples 1 to 8 were coated with the fluororesin paint of [Blend 4] below using a 100 mesh gravure roll, and then heated and dried in a hot air oven at 120°C for 2 minutes to harden the fluororesin paint of [Blend 4] to form an antifouling coating film layer (4 g / m2 ) were obtained as canvases (9) to (16). [Formulation 4] Fluorine-based resin paint (for forming antifouling coating layer) Hydroxyl-containing fluoroolefin vinyl ether copolymer (fluorine-based resin) 100 parts by mass Isocyanurate trimer of hexamethylene diisocyanate (isocyanate) 10 parts by mass Colloidal silica (antistatic) 8 parts by weight Triazine tautomer (ultraviolet absorber) 5 parts by weight Curing catalyst: Dibutyltin dilaurate (approximately 10 ppm for fluororesin) Toluene / butyl acetate (diluent with a mass ratio of 1:1) 400 parts by mass

[0043] [Example 17] The mass was 470 g / m, which was the same as Example 1, except that the blend 1 in Example 1 was changed to blend 5. 2 A canvas (17) was obtained. Blend 5 is a blend in which 4 parts by mass of silicone resin powder (lubricant) in Blend 1 is omitted. The canvas (17) that does not contain silicone resin powder (lubricant) in the soft polyvinyl chloride resin impregnated coating layer tends to be slightly inferior in flexural durability (Scott flexural abrasion test and De Mattia flexural fatigue test) to the canvas (1) of Example 1 due to the increased friction coefficient of the soft polyvinyl chloride resin impregnated coating layer, but the basic performance was comparable to that of the canvas (1) of Example 1.

[0044] [Table 1]

[0045] [Table 2]

[0046] The canvases (1) to (8) of Examples 1 to 8 all used fabrics with twisted yarns of bulky multifilament yarns (Taslan processed yarns or core spun core-sheath processed yarns) and staple spun yarns as warp yarn groups and weft yarn groups, which strengthened and stabilized the adhesion between the fabric and the soft polyvinyl chloride resin-impregnated coating layer, resulting in excellent flexural durability (flutter resistance). In particular, the soft polyvinyl chloride resin-impregnated coating layer was compounded with a synthetic rubber cured product, and the synthetic rubber cured product was formed by coating the fabric with a soft polyvinyl chloride resin composition containing liquid synthetic rubber, converting the liquid synthetic rubber into a rubber cured product, and compounding the synthetic rubber cured product over the entire area of ​​the soft polyvinyl chloride resin-impregnated coating layer, which is a special product. Immediately after application, the soft polyvinyl chloride resin-impregnated coating layer contains liquid rubber molecular chains entangled with the polyvinyl chloride resin main chains. In the next process, the liquid synthetic rubber is hardened so that the rubber molecular chains are spread throughout the entire soft polyvinyl chloride resin-impregnated coating layer, and by building a network in which they are entangled with the polyvinyl chloride resin main chains in particular, it is possible to obtain a canvas for industrial use that has excellent flexural durability (flutter resistance), particularly in terms of flexural durability below freezing (Scott flex abrasion test and De Mattia flexural fatigue test), and heat resistance under the hot sun (heat creep test for joints). In particular, in the canvases of Examples 2, 5, and 8, the liquid synthetic rubber bonds (through a crosslinking agent) with the silanol groups (Si-OH groups) on the surface of the silica particles, and the structure of the rubber cured product contains silica (treated with a silane coupling agent) at the intermediate point, which strengthens the rubber cured product and further improves its flexural durability (Dematcia flexural fatigue test) and abrasion resistance (Scott flexural abrasion test), as well as the cold resistance and heat resistance (bonding heat creep test) of the soft polyvinyl chloride resin impregnated coating layer. The canvases (9) to (16) of Examples 9 to 16 have a fluorine-based resin antifouling coating film layer formed on the surface of the canvases (1) to (8) of Examples 1 to 8, and the cleaning and wiping removal of soot and dust stains that adhere and accumulate during outdoor use (outdoor exposure from March to September 2023: Soka City, Saitama Prefecture) is much better than the canvases (1) to (8) of Examples 1 to 8, and is as easy as a whiteboard.

[0047] [Comparative Example 1] The fabric (1) in Example 1 was changed to fabric (9), and the fabric was the same as Example 1, with a mass of 453 g / m 2 The result was canvas (18). <Fabric (9)> The warp and weft yarns are made of polyester 1111 dtex (192 filaments) multifilament yarn (125 twists / m taslan textured yarn). The warp yarns have a thread density of 33 threads / inch and the weft yarns have a thread density of 30 threads / inch. The fabric is woven in a plain weave with a void ratio of 12% and a mass of 198 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. The resulting canvas (18) used multifilament yarns for both the warp and weft groups, which was effective in providing adhesion (anchor effect) to the soft polyvinyl chloride resin-impregnated coating layer. However, the anchor effect was not as good as that of staple spun yarns. In the bending durability test (Scott bending abrasion test and De Mattia bending fatigue test), the soft polyvinyl chloride resin-impregnated coating layer peeled off from the fabric (9). In the heat resistance test (heat creep test at joints), not only did the fabric suffer from failure due to yarn pull-out, but the tear strength was inferior to that of the canvas (1) of Example 1, due to the use of less twisted Taslan-processed yarn to achieve the anchor effect.

[0048] [Comparative Example 2] The fabric (1) in Example 1 was changed to fabric (10), and the fabric was the same as Example 1, with a mass of 486 g / m 2 The result was canvas (19). <Fabric (10)> The warp and weft yarns were made of polyester 10-count two-ply yarn (1180 dtex: twist count 330 turns / m) staple fiber spun yarns, and the warp yarns had a thread density of 33 threads / inch and the weft yarns had a thread density of 30 threads / inch. The fabric was woven in a plain weave with a void ratio of 5% and a mass of 231 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. The resulting canvas (19) used short fiber spun yarns for both the warp and weft thread groups, which was effective in providing adhesion (anchor effect) to the soft polyvinyl chloride resin impregnated coating layer and had better flexural durability (Scott flex abrasion test / De Mattia flexural fatigue test) than the canvas (1) of Example 1. However, because only short fiber spun yarns were used to achieve the anchor effect, the tear strength was inferior to the canvas (1) of Example 1, and the heat resistance (heat creep test at joints) was such that the yarns broke.

[0049] [Comparative Example 3] The fabric (1) in Example 1 was changed to fabric (11), and the fabric was the same as Example 1, with a mass of 470 g / m 2 of Canvas (20). <Fabric (11)> The warp and weft yarns are made of polyester 555 dtex (96 filaments) multifilament yarn (twist count 20 times / m: no taslan processing) and polyester 20-count two-ply yarn (590 dtex: twist count 200 times / m) short fiber spun yarn (twist count 125 times / m). The warp yarn density is 33 threads / inch and the weft yarn density is 30 threads / inch. The void ratio is 8% and the mass is 215 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. The resulting canvas (20) used straight multifilament yarns that had not been Taslan-processed in the twisted components, and therefore had inferior adhesion (anchor effect) to the soft polyvinyl chloride resin-impregnated coating layer compared to the canvas (1) of Example 1. In the bending durability test (Scott bending abrasion test and De Mattia bending fatigue test), the soft polyvinyl chloride resin-impregnated coating layer peeled off slightly from the fabric (11). In the heat resistance test (heat creep test at joints), failure due to thread pull-out occurred. However, because Taslan-processed yarns were not used, the tear strength was slightly better than that of the canvas (1) of Example 1.

[0050] [Comparative Example 4] The fabric (1) in Example 1 was changed to fabric (12), and the fabric was the same as Example 1, with a mass of 470 g / m 2 The result was canvas (21). <Fabric (12)> The warp and weft yarns were made of polyester 555 dtex (96 filaments) multifilament yarn (twist count 20 times / m: no taslan processing) and polyester 10 count single yarn (590 dtex: twist count 200 times / m) staple spun yarn (twist count 125 times / m). The warp yarns had a thread density of 33 threads / inch and the weft yarns had a thread density of 30 threads / inch. The void ratio was 8% and the mass was 215 g / m. 2 The fabric (water-repellent treatment was the same as in Example 1) was used. The resulting canvas (21) used straight multifilament yarn that had not been Taslan-processed in the twisted component, and therefore had inferior adhesion (anchor effect) to the soft polyvinyl chloride resin-impregnated coating layer compared to the canvas (1) of Example 1. In the bending durability test (Scott flex abrasion test and De Mattia flex fatigue test), the soft polyvinyl chloride resin-impregnated coating layer peeled off slightly from the fabric (12). In the heat resistance test (heat creep test at joints), failure due to thread pull-out occurred. However, because Taslan-processed yarn was not used, the tear strength was slightly better than that of the canvas (1) of Example 1.

[0051] [Table 3]

[0052] [Comparative Example 5] The mass was 503 g / m, which was the same as Example 1, except that the blend 1 in Example 1 was changed to Blend 6. 2 The canvas (22) was obtained. Blend 6 is a blend that omits 10 parts by mass of butadiene liquid rubber (having -COOH groups at both ends of the molecule and an average molecular weight of 3000) and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinking agent) from Blend 1. Compared to the canvas (1) of Example 1, the canvas (22) was clearly inferior in flexural durability at room temperature and below freezing point (Scott flexural abrasion test and De Mattia flexural fatigue test) and in heat resistance under the hot sun (joint heat creep test), due to the lack of a rubber structure throughout the soft polyvinyl chloride resin impregnated coating layer.

[0053] [Comparative Example 6] The mass was 468 g / m, which was the same as Example 1, except that the blend 1 in Example 1 was changed to Blend 7. 2A canvas (23) of the above was obtained. In Blend 7, 10 parts by mass of the butadiene liquid rubber (having -COOH groups at both ends of the molecule and an average molecular weight of 3000) of Blend 1 was replaced with 10 parts by mass of butadiene rubber powder (registered trademark "Kane Ace" M-711: Kaneka Corporation), and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinking agent) were omitted. The butadiene rubber powder (non-crosslinked) was incompatible dispersed in the soft polyvinyl chloride resin impregnated coating layer, and due to the cold resistance of the butadiene rubber itself, it was slightly better than the canvas (22) of Comparative Example 5 in terms of bending durability (Scott bending abrasion test and De Mattia bending fatigue test) at sub-zero temperatures (not as good as the canvas (1) of Example 1), but numerous cracks were generated due to the influence of the incompatible dispersion. In addition, regarding heat resistance (heat creep test of joint), no particular improvement was observed compared to the canvas (22) of Comparative Example 5.

[0054] [Comparative Example 7] The mass was 468 g / m, which was the same as Example 1, except that the blend 1 in Example 1 was changed to Blend 8. 2 A canvas (24) of the above was obtained. In Blend 8, 10 parts by mass of the butadiene liquid rubber (having -COOH groups at both ends of the molecule and an average molecular weight of 3000) of Blend 1 was replaced with 10 parts by mass of a butadiene liquid rubber having no functional groups at both ends of the molecule and an average molecular weight of 3000, and 2 parts by mass of isocyanurate (HMDI trimer: NCO crosslinker) was omitted. The butadiene liquid rubber having no functional groups remained in the liquid state in the soft polyvinyl chloride resin impregnated coating layer, and exerted the effect of lowering the glass transition temperature of the polyvinyl chloride resin, and thus had better flexural durability (Scott flexural abrasion test and De Mattia flexural fatigue test) below freezing point than the canvas (22) of Comparative Example 5 (same as the canvas (1) of Example 1), but on the other hand, the presence of the butadiene liquid rubber had a negative effect on heat resistance (heat creep test of joints), and the results were inferior to the canvas (18) of Comparative Example 1.

[0055] [Comparative Example 8] The same as in Example 1 was performed except that the fabric (1) in Example 1 was changed to the fabric (10) and that the blend 1 was changed to the blend 6. However, the impregnated coating amount of the blend 6 was 253 g / m 2 from 300 g / m2 The weight has been increased to 530g / m 2 The canvas (25) was a No. 5 canvas class canvas, and the No. 6 canvas (about 470 g / m) of Examples 1 to 8 and Comparative Examples 1 to 7 was obtained. 2 ) class, the soft polyvinyl chloride resin impregnated coating layer is 60g / m 2 Due to the large design, the evaluation in the Scott type reciprocating bending abrasion test 3000 times was better than Comparative Examples 1, 3, and 4 to 6 and equivalent to Examples 1, 3, 4, 6, and 7, but the weight was increased by one rank, making it unnecessarily difficult to transport and handle.

[0056] [Table 4] [Industrial Applicability]

[0057] As is clear from the above examples and comparative examples, according to the present invention, a canvas for industrial materials is obtained that has excellent bending durability (resistance to flapping) and abrasion resistance, especially bending durability (resistance to flapping) at sub-freezing points and joint durability under the hot sun (resistance to peeling at sewn parts).It is also possible to reduce the weight by one rank without sacrificing performance, allowing for a wide range of uses as the main material for tent warehouses (simple houses), roofed tents (assembly tents with awnings used for sports days, outdoor events, management headquarters, assemblies, reception desks, etc.), truck canopies, truck bed covers, and open-air storage sheets.

Claims

1. A canvas for industrial materials, comprising a soft polyvinyl chloride resin-impregnated coating layer provided on the entire surface of the fabric, the fabric being woven from a warp yarn group and a weft yarn group, the warp and weft yarn groups being composed of a multifilament yarn / staple fiber spun yarn combined and twisted, the multifilament yarn being a bulky yarn or a twisted yarn having a bulky portion on its outer periphery, the soft polyvinyl chloride resin-impregnated coating layer containing a cured liquid rubber, the cured liquid rubber being a polymer of one or more reactive liquid rubbers selected from butadiene-based, isoprene-based, and farnesene-based, and a composite of the reactive liquid rubber and silica particles, which is a reaction product with silanol groups (Si-OH groups) on the surface of the silica particles.

2. The canvas for industrial materials according to claim 1, wherein the soft polyvinyl chloride resin impregnated coating layer contains silicone microparticles, and the silicone microparticles are one or more types selected from silicone rubber powder, silicone resin powder, hydrophobic silica powder, grafted silicone powder, and composite powder in which the surface of silicone rubber particles is coated with silicone resin.

3. A method for producing canvas for industrial materials, which is composed of composite yarn of multifilament yarn / staple fiber spun yarn and has a soft vinyl chloride resin-impregnated coating layer formed on the entire surface of the fabric, comprising the steps of: 1) preparing a soft vinyl chloride resin composition containing at least three components: vinyl chloride resin, a plasticizer, and a reactive liquid synthetic rubber (one or more selected from butadiene-based, isoprene-based, and farnesene-based). 2) applying the soft vinyl chloride resin composition to the fabric to form a soft vinyl chloride resin-impregnated coating layer (before gelation). 3) simultaneously with the gelation heat treatment of the soft vinyl chloride resin composition to form the soft vinyl chloride resin-impregnated coating layer, converting the reactive liquid synthetic rubber into a rubber cured product to impregnate the entire soft vinyl chloride resin-impregnated coating layer with synthetic rubber components.

4. A manufacturing method for canvas for industrial materials as described in claim 3, wherein the fabric is woven from a warp yarn group and a weft yarn group, both of which are composed of twisted yarns of multifilament yarns / staple fiber spun yarns, and the multifilament yarns are bulky yarns or twisted yarns having a bulky portion on the outer periphery.

5. 4. The method for producing canvas for industrial materials according to claim 3, wherein the soft polyvinyl chloride resin composition is made to contain silica particles and converted into a composite rubber cured product with the silica particles.

Citation Information

Patent Citations

  • JP1978056080U

  • Sheet-shaped material and its manufacture

    JP1984103750A

  • Sheet

    JP1998096168A

  • Soft vinyl chloride resin-made industrial material sheet

    JP2015205428A

  • Industrial material canvas excellent in tear strength

    JP2021017668A